A concrete composite admixture, its preparation method and application

CN121248322BActive Publication Date: 2026-10-27HUNAN CSCEC5B CONCRETE +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511175708.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2026-10-27
Estimated Expiration
2045-08-21

AI Technical Summary

Technical Problem

[0003]为了解决上述问题,传统技术中常采用三类技术手段,其一是表面物理隔绝,例如形成涂层,隔绝除冰液的内渗,避免其影响;但是涂层一旦破损,被涂层保护的混凝土性能会快速劣化,该方法的耐久性差,且需要严格的后期维护;其二是在混凝土中补充添加剂,主要包括引气剂,以为内渗水结冰后的体积变化提供空间;其三是调整混凝土的基本配方,例如,骨料的种类、骨料的用量、水灰比等;但是添加外加剂或者调整混凝土的基本配方,对抗盐抗冻性能的提升不明显

Benefits of technology

[0011]所述减水剂可减少混凝土中水的用量,降低水灰比;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005559379320000061
    Figure BDA0005559379320000061
  • Figure BDA0005559379320000071
    Figure BDA0005559379320000071
  • Figure FDA0005559379310000011
    Figure FDA0005559379310000011
Patent Text Reader

Abstract

The application discloses a concrete composite admixture, a preparation method and application thereof, and belongs to the technical field of concrete admixtures.The concrete composite admixture comprises a water reducing agent, an alcohol amine, modified fly ash and a first Vinsol resin; the modified fly ash comprises a fly ash base body, and a second Vinsol resin is decorated on the fly ash base body.The concrete composite admixture can effectively improve the frost resistance and salt freeze-thaw resistance of concrete.The application further provides the preparation method and application of the concrete composite admixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete admixture technology, and in particular to a composite concrete admixture, its preparation method, and its application. Background Technology

[0002] De-icing fluids are widely used in civil airports, but they can cause salt-frost damage to concrete pavements. Salt-frost damage reduces pavement smoothness, affecting aircraft stability and comfort during takeoff and landing. If not repaired promptly, it can lead to more severe cracking of the concrete and structural damage. In other words, concrete pavements, such as airport pavements, that require frequent application of de-icing fluids need to be frost-resistant in saline environments.

[0003] To address these issues, traditional techniques often employ three types of methods. The first is surface physical isolation, such as forming a coating to prevent the de-icing fluid from seeping inwards and thus avoiding its impact. However, once the coating is damaged, the performance of the concrete protected by the coating deteriorates rapidly. This method has poor durability and requires strict post-concrete maintenance. The second is adding additives to the concrete, mainly air-entraining agents, to provide space for volume changes after the seeping water freezes. The third is adjusting the basic concrete formula, such as the type and amount of aggregate, and the water-cement ratio. However, adding admixtures or adjusting the basic concrete formula does not significantly improve salt resistance and freeze-thaw resistance.

[0004] Therefore, it is very important to improve the salt freeze-thaw resistance of concrete such as airport pavements. Summary of the Invention

[0005] This invention aims to at least solve one of the technical problems existing in the prior art. To this end, this invention proposes a concrete admixture that can effectively improve the freeze-thaw resistance and salt freeze-thaw resistance of concrete.

[0006] The present invention also provides a method for preparing the above-mentioned concrete composite admixture.

[0007] This invention also provides the application of the above-mentioned concrete composite admixture.

[0008] According to an embodiment of a first aspect of the present invention, a concrete composite admixture is provided, the components of which include a water-reducing agent, an alkanolamine, modified fly ash, and a first Vinsol resin;

[0009] The modified fly ash includes a fly ash matrix and a second Vinsol resin modified on the fly ash matrix.

[0010] The concrete composite admixture according to embodiments of the present invention has at least the following beneficial effects:

[0011] The water-reducing agent can reduce the amount of water used in concrete and lower the water-cement ratio;

[0012] The alkanolamine can be adsorbed onto the surface of metals such as steel bars to a certain extent, blocking the corrosion of metals by salt ions such as chloride ions.

[0013] After the fly ash matrix is ​​hydrated and cured for a long period of time (about 28 days), it can release active aluminum ions to participate in the formation of tricalcium aluminate. When it comes into contact with chloride ions and other salt ions, it can fix the chloride ions, preventing them from being free in water and causing serious freeze-thaw expansion problems, and also preventing them from being free to the metal surface and promoting metal corrosion.

[0014] Firstly, Vinsol resin has air-entraining capabilities, which can generate uniform bubbles. These bubbles act as "pressure buffer chambers" during freeze-thaw cycles, providing space for ice crystal expansion, effectively releasing internal pressure, and preventing damage to concrete structures.

[0015] The second Vinsol resin contained in the modified fly ash does not destroy its ring structure and still has free functional groups, thus it also has a certain air-entraining capacity; thereby, it can reduce the amount of the first Vinsol resin to a certain extent; and further improve the uniformity of the air bubbles themselves and the spacing between air bubbles in the later concrete.

[0016] The second Vinsol resin in the modified fly ash has the same structure as the first Vinsol resin. During use, they may be enriched to a certain extent and produce a synergistic effect. Specifically, when the liquid containing chloride ions enters the air bubbles generated by the air-entraining agent, the chloride ions are adsorbed / fixed by the fly ash or its products, thereby increasing the freezing point of the liquid and effectively alleviating the concrete peeling problem caused by salt freezing.

[0017] In summary, the concrete composite admixture provided by this invention has multiple functions, including physical isolation, chemical fixation, bubble generation, and reduced water consumption. It can significantly improve the resistance of concrete to salt freeze-thaw cycles and ultimately effectively extend the service life of concrete.

[0018] According to some embodiments of the present invention, the components of the concrete composite admixture, by weight, include:

[0019] The water-reducing agent is used in amounts of 0.05 to 0.15 parts; for example, it can be 0.05 parts, 0.08 parts, 0.1 parts, 0.12 parts, or 0.15 parts; or a range of values ​​consisting of any two of the above points.

[0020] The amount of alcohol amine is 1.5 to 2.5 parts; for example, it can be 1.5 parts, 1.8 parts, 2.0 parts, 2.2 parts, or 2.5 parts; or a range of values ​​consisting of any two of the above points.

[0021] 20-30 parts of modified fly ash; for example, specifically 20 parts, 22 parts, 25 parts, 28 parts, or 30 parts; or a range of values ​​consisting of any two of the above points;

[0022] The first Vinsol resin is 0.01 to 0.02 parts; for example, it can be 0.01 parts, 0.012 parts, 0.015 parts, 0.018 parts, or 0.02 parts; or a range of values ​​composed of any two of the above points.

[0023] According to some embodiments of the present invention, the water-reducing agent includes at least one of polycarboxylate water-reducing agents and naphthalene-based water-reducing agents.

[0024] According to some embodiments of the present invention, the alkanolamine includes at least one of diethanolamine, triethanolamine, and monoethanolamine.

[0025] According to some embodiments of the present invention, the fly ash matrix is ​​Grade I fly ash or Grade II fly ash.

[0026] Both the first Vinsol resin and the second Vinsol resin are resin pyrolysis products.

[0027] According to an embodiment of a second aspect of the present invention, a method for preparing the concrete composite admixture described in the first aspect of the present invention is provided, the preparation method comprising the following steps:

[0028] S1. In humid air, fly ash matrix, silane coupling agent and second Vinsol resin are mixed and reacted in an anhydrous solvent to obtain the modified fly ash; the silane coupling agent contains amino groups;

[0029] S2. Mix the modified fly ash, water-reducing agent, alkanolamine and first Vinsol resin.

[0030] The mechanism of the preparation method is as follows:

[0031] The fly ash matrix has silanol groups, and the rosin has carboxyl groups; the amino groups on the silane coupling agent and the carboxyl groups on the rosin can form amide bonds; the silanol groups after hydrolysis of the silane coupling agent and the silanol groups on the fly ash matrix dehydrate to form Si-O-Si covalent bonds; thereby, the chemical bonding between the first Vinsol resin and the fly ash matrix can be achieved.

[0032] Since the preparation method adopts all the technical solutions of the concrete composite admixture in the above embodiments, it has at least all the beneficial effects brought about by the technical solutions in the above embodiments.

[0033] According to some embodiments of the present invention, in step S1, the humidity of the humidified air is ≥80%; for example, it can be 80%, 85%, 90%, 95%, 100%; or a range of values ​​composed of any two of the above points.

[0034] According to some embodiments of the present invention, in step S1, the silane coupling agent includes at least one of KH550 and γ-aminopropyltrimethoxysilane (KH540).

[0035] According to some embodiments of the present invention, in step S1, the anhydrous solvent is at least one selected from anhydrous ethanol, anhydrous propanol, and anhydrous isopropanol. Wherein, "anhydrous" means that the water content is ≤0.001% by mass.

[0036] According to some embodiments of the present invention, in step S1, the mass ratio of the fly ash matrix and the second Vinsol resin is 20-30:0.1-0.2. Specifically, it can be 20:0.1, 20:0.2, 30:0.1, 30:0.2, 25:0.1, 25:0.2, 25:0.15; or a range of values ​​consisting of any two of the above points.

[0037] According to some embodiments of the present invention, in step S1, the mass ratio of the silane coupling agent to the first Vinsol resin is 0.1 to 0.2:1. For example, it can specifically be 0.1:1, 0.12:1, 0.15:1, 0.18:1, 0.2:1; or a range of values ​​consisting of any two of the above points.

[0038] According to some embodiments of the present invention, in step S1, the mass-volume ratio of the fly ash matrix and the anhydrous solvent is 1g:2 to 6mL; for example, it can be 1g:2mL, 1g:3mL, 1g:4mL, 1g:5mL, 1g:6mL; or a range of values ​​composed of any two of the above points.

[0039] According to some embodiments of the present invention, in step S1, the duration of the mixing reaction is 1 to 3 hours; for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours; or a range of values ​​composed of any two of the above points.

[0040] According to some embodiments of the present invention, the preparation method further includes washing and drying the obtained solid after step S2. The washing method is alcohol washing, and the drying method includes vacuum drying.

[0041] According to some embodiments of the present invention, the preparation method is carried out at room temperature, that is, the actual temperature is between 15 and 30°C.

[0042] According to an embodiment of a third aspect of the present invention, a concrete formulation is provided, the concrete formulation comprising cement, aggregate, sand, water and the concrete composite admixture described in the first aspect of the present invention.

[0043] Since the concrete formula adopts all the technical solutions of the concrete composite admixtures in the above embodiments, it has at least all the beneficial effects brought about by the technical solutions in the above embodiments. That is, the specimens and buildings made from the concrete formula have excellent freeze-thaw resistance in chloride-containing environments.

[0044] According to some embodiments of the present invention, the concrete composite admixture accounts for 5-10% of the cement mass. For example, it can be 5%, 6%, 7%, 8%, 9%, 10%; or a range of values ​​composed of any two of the above points.

[0045] According to some embodiments of the present invention, the mass ratio of water to cement is 0.3 to 0.42:1. For example, it can be 0.3:1, 0.35:1, 0.4:1, 0.42:1; or a range of values ​​consisting of any two of the above points.

[0046] According to some embodiments of the present invention, the stones are crushed stones.

[0047] According to some embodiments of the present invention, the stones are pebbles.

[0048] According to some embodiments of the present invention, the aggregate includes a first aggregate and a second aggregate; the particle size distribution of the first aggregate is 5-20 mm; the particle size distribution of the second aggregate is 20-40 mm; the mass ratio of the first aggregate to the second aggregate is 1:3.5-4.5; thereby, a better gradation can be formed, and the density of the resulting concrete can be improved.

[0049] According to some embodiments of the present invention, the mass ratio of the gravel to cement is 7 to 8:1; for example, it can be 7:1, 7.5:1, 8:1; or a range of values ​​composed of any two of the above points.

[0050] According to some embodiments of the present invention, the mass ratio of the sand to the cement is 1 to 2:1; for example, it can be 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1; or a range of values ​​consisting of any two of the above points.

[0051] According to an embodiment of the fourth aspect of the present invention, a concrete composite admixture provided in the first aspect of the present invention, or the concrete formulation described in the third aspect of the present invention, is provided for use in the construction of airport pavement.

[0052] Since the application adopts all the technical solutions of the concrete composite admixture or concrete formula of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments.

[0053] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Detailed Implementation

[0054] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0055] Example 1

[0056] Referring to the formulation in Table 1, this example prepares a concrete composite admixture. The specific preparation process is as follows:

[0057] S1. In humid air, fly ash matrix, silane coupling agent, and second Vinsol resin are mixed and reacted in an anhydrous solvent, followed by solid-liquid separation, alcohol washing, and drying; modified fly ash is obtained; wherein,

[0058] The fly ash matrix is ​​Class II fly ash; the silane coupling agent is KH550; the second Vinsol resin was purchased from Shanghai Maitian Chemical Co., Ltd.; the anhydrous solvent is anhydrous ethanol.

[0059] The mass ratio of fly ash matrix to the second Vinsol resin is 25:0.15;

[0060] The mass ratio of silane coupling agent to the second Vinsol resin is 0.1:1;

[0061] The mass-to-volume ratio of fly ash matrix to anhydrous solvent is 1 g: 4 mL;

[0062] The reaction time was 1.5 hours; the temperature was room temperature, approximately 25°C.

[0063] The humidity of the humidifying air is 93%.

[0064] The mixing reaction is carried out under stirring. The purpose of stirring is to prevent the materials from agglomerating or the reaction from being uneven. Therefore, there is no strict limit to the stirring speed; it is sufficient to disturb the dispersion.

[0065] The solvent used for alcohol washing is anhydrous ethanol; the washing is performed 3 times.

[0066] The drying method is vacuum drying at a temperature of 70℃.

[0067] S2. Mix modified fly ash, water-reducing agent, alkanolamine and first Vinsol resin.

[0068] Table 1. Raw material ratios for the preparation of the concrete composite admixture in Example 1.

[0069] Water reducing agent Hunan Zhongyan Building Materials Technology Co., Ltd. / Self-compacting Concrete Water-reducing Agent 0.1 alcoholamines Diethanolamine (CAS: 111-42-2) 2 Modified fly ash This example 25 First Vinsol Resin Shanghai Maitian Chemical Co., Ltd. 0.015

[0070] Example 2

[0071] This example prepares a concrete composite admixture, which differs from Example 1 in that:

[0072] Specifically, the amount of modified fly ash used is 30 parts.

[0073] Example 3

[0074] This example prepares a concrete composite admixture, which differs from Example 1 in that:

[0075] In step S1, the mass ratio of fly ash matrix to the second Vinsol resin is 30:0.1.

[0076] Comparative Example 1

[0077] This example prepares a concrete composite admixture, which differs from Example 1 in that:

[0078] Replace the modified fly ash with an equal mass of fly ash matrix;

[0079] Furthermore, the first Vinsol resin has a weight part of 0.16.

[0080] Comparative Example 2

[0081] This example prepares a concrete composite admixture, which differs from Example 1 in that:

[0082] The components do not include alcohol amines.

[0083] Example 4

[0084] This example provides a concrete formula, the specific composition of which is shown in Table 2.

[0085] Table 2 Composition of concrete formula in Example 4

[0086] cement Xuzhou Huaihai Zhonglian Cement Co., Ltd. / P·O42.5 Silicate 100 pebbles Crushed stone / 5~20mm particle size : 20~40mm particle size = 1:4 750 sand natural river sand 180 water / 41 Concrete composite admixtures Example 1 8

[0087] Example 5

[0088] This example provides a concrete formula, which differs from Example 4 in that:

[0089] The concrete composite admixture is from Example 2.

[0090] Example 6

[0091] This example provides a concrete formula, which differs from Example 4 in that:

[0092] The concrete composite admixture is from Example 3.

[0093] Example 7

[0094] This example provides a concrete formula, which differs from Example 4 in that:

[0095] The stones used were pebbles, with the same particle size distribution as in Example 4.

[0096] Comparative Example 3

[0097] This example provides a concrete formula, which differs from Example 4 in that:

[0098] The concrete composite admixture was derived from Comparative Example 1.

[0099] Comparative Example 4

[0100] This example provides a concrete formula, which differs from Example 4 in that:

[0101] The concrete composite admixture was obtained from Comparative Example 2.

[0102] Test case

[0103] According to GB-T50082-2009 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete", the freeze-thaw performance of the concrete obtained in Examples 4-7 and Comparative Examples 3-4 was tested. The freeze-thaw test method adopted the rapid freezing method standard. The freeze-thaw test blocks were all 100×100×400mm in size. The freeze-thaw testing machine model was TDR-28, and the duration of each freeze-thaw cycle was 3 hours. The freeze-thaw environment was a 5% magnesium chloride solution. Before the formal start of the freeze-thaw test, the concrete test blocks were completely immersed in the 5% magnesium chloride solution for 4 days. After every 25 freeze-thaw cycles, the mass loss ratio and relative dynamic modulus of elasticity of the test block were measured. The mass loss ratio and relative dynamic modulus of elasticity were recorded after 300 cycles. The test results are shown in Table 3.

[0104] Table 3 shows the salt freeze-thaw resistance of the concrete formulations in the examples and comparative examples.

[0105]

[0106]

[0107] Table 3 shows that, within the scope provided by this invention, the concrete prepared by the obtained concrete composite admixture has excellent freeze-thaw resistance in a chloride solution environment.

[0108] Comparing the results of Examples 4 and 5, it can be seen that increasing the mass of modified fly ash is equivalent to increasing the mass of modified fly ash in the resulting concrete formula to a certain extent. The fly ash matrix has two functions in the concrete formula: one is to form intermediate products that can fix chloride ions, and the other is to fill gaps. However, filling gaps may form more capillary pores, which is detrimental to freeze-thaw performance. When the amount of fly ash matrix is ​​relatively small, the first function is dominant. As the amount of fly ash matrix increases, the proportion of the latter function gradually increases, so the freeze-thaw resistance effect will decrease slightly.

[0109] Comparing the results of Examples 4 and 6, it can be seen that if the mass ratio of the second Vinsol resin used in the modified fly ash decreases, the amount of resin contained in the modified fly ash decreases, which is insufficient to adjust the distribution of the fly ash matrix. Therefore, the fly ash is basically randomly distributed in the concrete, and the synergistic effect between the modified fly ash and the first Vinsol resin decreases. As a result, the overall freeze-thaw resistance of the obtained concrete formulation decreases slightly.

[0110] Comparing the results of Examples 4 and 7, it can be seen that using angular crushed stone is more beneficial to improving the freeze-thaw resistance of the resulting concrete formula than using smooth pebbles. This is because the surface smoothness of crushed stone is lower and the friction with the surrounding components is higher. Therefore, even if the volume of concrete (and its solution) changes during the freeze-thaw process, it still has a certain stress resistance and minimizes the peeling of concrete surface components.

[0111] The results of Example 4 and Comparative Example 3 show the same trend as those of Example 4 and Example 6. If the fly ash is not modified at all, the synergistic effect is lost and the performance of the resulting concrete is significantly reduced.

[0112] Comparing the results of Example 4 and Comparative Example 4, it can be seen that if the amine is omitted from the concrete composite admixture, the overall performance of the concrete will be reduced to a certain extent. This indicates that amine and other components also have a certain synergistic effect. Furthermore, this invention also investigated the freeze-thaw resistance of concrete specimens containing reinforcing steel. The results showed that after approximately 75 freeze-thaw tests, the reinforcing steel in the concrete specimens obtained in Comparative Example 4 showed significant corrosion; while the reinforcing steel in the examples showed almost no corrosion. This demonstrates that amine can indeed form a film on the surface of the reinforcing steel, thereby effectively mitigating chloride ion corrosion.

[0113] In summary, the concrete composite admixture provided by this invention can synergistically improve the freeze-thaw resistance of concrete in chloride-containing environments; it is precisely because of this property that the concrete composite admixture, or concrete formula, provided by this invention is expected to be widely used in the construction of airport pavements.

[0114] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A concrete composite admixture, characterized in that, The components of the concrete composite admixture include water-reducing agent, amine, modified fly ash and first Vinsol resin; The modified fly ash includes a fly ash matrix and a second Vinsol resin modified on the fly ash matrix.

2. The concrete composite admixture according to claim 1, characterized in that, The components of the concrete composite admixture, by weight, include:

3. The concrete composite admixture according to claim 1 or 2, characterized in that, The water-reducing agent includes at least one of polycarboxylate water-reducing agents and naphthalene-based water-reducing agents.

4. The concrete composite admixture according to claim 1 or 2, characterized in that, The alkanolamine includes at least one of diethanolamine, triethanolamine, and monoethanolamine.

5. A method for preparing a concrete composite admixture as described in any one of claims 1 to 4, characterized in that, The preparation method includes the following steps: S1. In humid air, fly ash matrix, silane coupling agent and second Vinsol resin are mixed and reacted in an anhydrous solvent to obtain the modified fly ash; the silane coupling agent contains amino groups; S2. Mix the modified fly ash, water-reducing agent, alkanolamine and first Vinsol resin.

6. The preparation method according to claim 5, characterized in that, In step S1, the mass ratio of the fly ash matrix to the second Vinsol resin is 20-30:0.1-0.2; And / or, the mass ratio of the silane coupling agent to the first Vinsol resin is 0.1 to 0.2:

1.

7. A concrete formula, characterized in that, The concrete formulation includes cement, aggregate, sand, water, and the concrete composite admixture as described in any one of claims 1 to 4.

8. The concrete formula according to claim 7, characterized in that, The concrete composite admixture accounts for 5-10% of the mass of the cement.

9. The concrete formula according to claim 7, characterized in that, The mass ratio of water to cement is 0.3 to 0.42:1; And / or, the stones are gravel.

10. The application of a concrete composite admixture as described in any one of claims 1 to 4, or a concrete formulation as described in any one of claims 7 to 9, in the construction of airport pavements.

Citation Information

Patent Citations

  • Building material manufacturing from fly ash

    US4659385A

  • Mixture of portland cement concrete materials for freeze / thaw resistance

    US5306344A